Monitoring connectivity in wireless sensor networks - Khelifa, B.; Haffaf, H.; Madjid, M.; Llewellyn-Jones, D. (2009 IEEE Symposium on Computers and Communications, 2009)
It is important to have continuous connectivity in a wireless sensor network after it is deployed in a hostile environment. However, such networks are constrained by the low user-to-node ratio, limited energy and bandwidth resources, entities that are usually mobile, networks without fixed infrastructure and frequent failure due to problems of energy, vulnerability to attack, etc. To address these difficulties, there is a need for wireless sensor networks to be self-organizing and self-configuring so as to improve performance, increase energy efficiency, save resources and reduce data transmission. In this paper, we present a method for monitoring, maintaining and repairing the communication network of a dynamic mobile wireless sensor network, so that network connectivity is continuously available and provides fault tolerance. Specifically, we propose an algorithm for the detection and surveillance of articulation points in graph connectivity, including an algorithm for network auto-organization in the event that this occurs.